Hidden Behind Homonymy: Infamy or Sanctity? - Jewgienij Zubkow (Religions, 2025)
This research focuses on the ideological sphere of criminals with the highest status in the Russian Federation. This ideological sphere was studied in literary sources of various kinds on the basis of repeatability (the existence of linguistic facts) and averaging (external and internal confrontation of sources). It is suggested that, in speech, there exist some selective overinterpretations of world religions that neglect basic elements of the traditional law-abiding picture of the world and that are directly based on literary fiction instead of the scientific literature. On the other hand, there can be some search for faith connected with the belief in spiritual knowledge from the dead, divine beings, and God.